Analisis Kesulitan Belajar Siswa pada Mata Pelajaran Kelistrikan Otomotif Siswa Kelas XI Jurusan Teknik Kendaraan Ringan di SMK N 4 Lhokseumawe - Heri Fahmi Ramadhan; Abubakar Abubakar; Siraj Siraj; Jumadi Jumadi; Nuraina Nuraina (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This research aims (1) to determine the internal and external factors that cause learning difficulties for students majoring in TKRO at SMK N 4 Lhokseumawe, (2) to find out learning strategies that can help class XI students majoring in TKRO at SMK N 4 Lhokseumawe. This research is descriptive qualitative research. Data was obtained through observation, interviews, documentation. The research subjects were class XI students majoring in light vehicle engineering at SMK N 4 Lhokseumawe. Research data was analyzed using data reduction analysis methods, data presentation, and drawing conclusions. Based on the results of interviews with class Factors that cause learning difficulties include the classroom atmosphere, the way the teacher teaches, and students' internal factors such as physiology and psychology. So this research was conducted with the aim of analyzing and finding strategies to overcome students' learning difficulties. The results of the study with an average acquisition of student learning difficulties of 2.648 are included in the High category. With the qualification of learning difficulties for automotive electrical material is